Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Learning dense gas-solids flows with physics-encoded neural network model - Xiaolin Guo; Chenshu Hu; Yuyang Dai; Hongbo Xu; Lingfang Zeng (Chemical Engineering Journal, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Molecular understanding on ultraviolet photolytic degradation of cyano liquid crystal monomers - Enya Wu; Hanchun Chen; Lingfang Tang; Lixi Zeng; Haodong Ji; Mingshan Zhu (Journal of Hazardous Materials, 2024)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

Genome resequencing-based high-density genetic map and QTL detection for yield and fiber quality traits in diploid Asiatic cotton (Gossypium arboreum) - Yaohua Li; Tong Mo; Lingfang Ran; Jianyan Zeng; Chuannan Wang; Aimin Liang; Yonglu Dai; Yiping Wu; Ziman Zhong; Yuehua Xiao (Molecular Genetics and Genomics, 2022)

Analysis and mapping quantitative trait loci for histidine content in barley (Hordeum vulgare L.) using microsatellite markers - Lingfang Yan; Xiaomeng Yang; Zhenghai Sun; Juan Du; Xiaoying Pu; Jiazhen Yang; Yawen Zeng (Genetic Resources and Crop Evolution, 2021)
Mining the gene of histidine content in barley grain helps with the breeding of functional barley varieties. The study constructed a recombinant inbred lines (RILs) containing 193 families derived from the cross between Ziguangmangluoerling (ZGMLEL) (♀) and Schooner No.3 (♂). The histidine (HIS) content in the grain of the mapping population and its parents were determined by an automatic amino acid analyzer. The HIS content of ZGMLEL was 0.53 mg/g. The grain HIS content of Schooner No. 3 was 0.21 mg/g, and the grain HIS content of population ranged from 0.23 to 0.54. Genetic linkage maps, including those of seven chromosomes of barley, were constructed by using 180 pairs of simple sequence repeat (SSR) markers, with a total genetic distance of 2671.03 cM and average marker spacing of 14.84 cM. Quantitative trait locus (QTL) IciMappingV3.3 was used to analyze QTL of HIS content in barley grains, and three QTLs were detected. Mapping results showed that the three loci were located on chromosomes 2H, 4H, and 7H, respectively. The major QTL with a contribution rate of 10.11% was located on barley chromosome 4H (HVBAMMGB84-BMAG0808). The additive effect is positive (0.025). Thus, it comes from the high-value parent ZGMLEL. Another major QTL with a contribution rate of 13.75% was located on barley chromosome 7H (GBM1303-GMS056). The minor QTL with a contribution rate of 6.01% was located on chromosome 2H (Scssr03381-Scssr07759). The additive effects of 4H and 7H QTLs were negative (− 0.02 and − 0.033). So, they came from the male parent Schooner. The results provided a reference for further fine mapping, cloning, and transformation of HIS genes in barley grains.

Analysing changes of the Poyang Lake water area using Sentinel-1 synthetic aperture radar imagery - Lingfang Zeng; Michael Schmitt; Lin Li; Xiao Xiang Zhu (International Journal of Remote Sensing, 2017)